2019
DOI: 10.7567/1347-4065/ab106b
|View full text |Cite
|
Sign up to set email alerts
|

InAlN-based LEDs emitting in the near-UV region

Abstract: Fully functional InAlN-based ultraviolet LEDs emitting at 340–350 nm were demonstrated for the first time; detailed electrical and optical characterization is presented and discussed. Results from the measurements at pulsed conditions are in agreement with the attribution of the dominant electroluminescence peak to near-band-edge emission. The composition of the AlGaN barriers was chosen to give the same internal polarization field as that of the InAlN wells. A simulation study of this polarization-matched het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…These results mean that average x of the nanoboards are almost homogeneous but x has remarkable inhomogeneity with the length scale shorter than a few nm. This local inhomegeneity produces remarkable E g inhomogeneity, because Al 1− x In x N alloys of low to middle x have high derivative dE g( x )/ dx value, which causes large alloy broadening 23 , 24 , 28 35 . In the present nanoboards, E g for x = 0.26 and 0.35 are estimated according to Refs.…”
Section: Results: Compositional Superlattices (Csls) In a Pseudomorphmentioning
confidence: 99%
See 3 more Smart Citations
“…These results mean that average x of the nanoboards are almost homogeneous but x has remarkable inhomogeneity with the length scale shorter than a few nm. This local inhomegeneity produces remarkable E g inhomogeneity, because Al 1− x In x N alloys of low to middle x have high derivative dE g( x )/ dx value, which causes large alloy broadening 23 , 24 , 28 35 . In the present nanoboards, E g for x = 0.26 and 0.35 are estimated according to Refs.…”
Section: Results: Compositional Superlattices (Csls) In a Pseudomorphmentioning
confidence: 99%
“…For the urgent development of DUV LEDs, Al x Ga 1− x N alloys have been studied and great strides have been achieved 11 19 . Beyond Al x Ga 1− x N, the use of immiscible 7 , 10 , 20 – 22 Al 1− x In x N alloys is an exotic way for realizing light-emitters 23 , 24 operating in DUV to infrared wavelengths, because their bandgap energies ( E g ) cover from DUV ( E g = 6.01 eV for AlN) to infrared ( E g = 0.65 eV for InN) wavelengths. However, c -plane Al 0.82 In 0.18 N epilayers lattice-matched to GaN have been exclusively investigated as auxiliary components such as Al 0.82 In 0.18 N/GaN distributed Bragg reflectors 25 and an Al 0.82 In 0.18 N barrier for GaN heterostructure field-effect transistors 26 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, high quality InAlN LEDs and power devices with lower indium compositions have been achieved. Anna et al reported the In0.14Al0.86N /AlN/GaN high electron mobility transistor (HEMT) [44] and Pietro et al fabricated the UVA LED with In0.14Al0.86N polarization matched quantum well [45]. Thus, we believe our design could effectively improve the polarization issue in AlGaN-based UV LED without introducing complex structures and growth techniques.…”
Section: (B) Besides > Replace This Line With Your Manuscript Id Number (Double-click Here To Edit) <mentioning
confidence: 87%